2008
DOI: 10.1242/dev.016386
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofseven-upfromDrosophilaR1/R6 photoreceptors reveals a stochastic fate choice that is normally biased by Notch

Abstract: Recent evidence suggests that stochasticism is important for generating cell type diversity. We have identified a novel stochastic fate choice as part of the mechanism by which Delta/Notch (Dl/N) signaling specifies R7 fate in the Drosophila eye. The equivalence of R1/R6/R7 precursors is normally broken by the activation of N, which specifies the R7 fate. The orphan nuclear hormone receptor Seven-up (Svp) is necessary and sufficient to direct R1/R6/R7 precursors to adopt the R1/R6 fate. A simple model, therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
(83 reference statements)
1
42
0
Order By: Relevance
“…It has also been reported that the differentiation of these photoreceptors is purely stochastic and independent (11). Recent studies (12,13) have identified a mutual inhibitory gene regulation motif as the core system driving the stochastic differentiation, but the exact mechanism of the stochastic differentiation is still unknown. The similarities between this natural system and our engineered system, both in terms of observation and underlying GRN, suggest that stochastic and irreversible cellular developments in the fruit fly eye could be due to initialization of cells near basin boundaries of a multistable network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the differentiation of these photoreceptors is purely stochastic and independent (11). Recent studies (12,13) have identified a mutual inhibitory gene regulation motif as the core system driving the stochastic differentiation, but the exact mechanism of the stochastic differentiation is still unknown. The similarities between this natural system and our engineered system, both in terms of observation and underlying GRN, suggest that stochastic and irreversible cellular developments in the fruit fly eye could be due to initialization of cells near basin boundaries of a multistable network.…”
Section: Discussionmentioning
confidence: 99%
“…Few mechanisms, however, have been proposed to explain the scenario of random and yet irreversible cell fate determination, which is commonly seen in development and cell differentiation. Recent studies (11)(12)(13) show examples of stochastic and irreversible cell differentiation in multicellular organisms, and they have identified that the central regulatory motif driving these stochastic differentiations is a mutual inhibitory gene regulatory network (GRN), a common topological module that can generate bistability. However, with neither fluctuating environmental cues nor spontaneous state transitioning identified in these cases, an understanding of how cells differentiate stochastically and irreversibly into distinct subpopulations remains elusive, especially when under the tight control of GRNs.…”
mentioning
confidence: 99%
“…These signals are necessary to activate pros and repress svp expression, respectively (Kauffmann et al, 1996;Miller et al, 2008;Xu et al, 2000). As the cone-cell precursor cells do not contact the determined R8 cell at the appropriate time, they will not 'see' the SEV ligand BOSS (Van Vactor et al, 1991).…”
Section: The Two-signal Model For R7-fate Determinationmentioning
confidence: 99%
“…When emc is absent, R7 precursors transform into R1/6 types, and so it appears to be a critical component of the N-induced R7 specification. 19 Another gene, seven-up (svp), encodes a steroid receptor-like protein that inhibits R7 development in R1/6/3/4 cells, 20 and is transcriptionally inactivated in R7 precursors by N, 21 while another gene, prospero (pros), encodes a homeodomain protein that prevents R7 precursors from adopting the R8 features, 22 and is transcriptionally regulated by N activity. 23 ommatidial development become photoreceptors.…”
Section: An Evolutionary Perspectivementioning
confidence: 99%